Clinical presentation and management of Tolosa-Hunt syndrome: a case report - Bisma Qasim; Farnaz Siddiqui; Maria Saleem; Muhammad Zohaib; Muhammad Khuzzaim Khan; Nisar Ahmed Siyal (Journal of the Pakistan Medical Association, 2024)
Tolosa-Hunt Syndrome (THS) is an exceptionally rare disorder characterised by recurrent episodes of excruciating ophthalmoplegia, commonly affecting one side of the face and involving the third, fourth, sixth, and fifth cranial nerves. This syndrome results from non-specific inflammation affecting the cavernous sinus, superior orbital fissure (SOF), and/or orbital apex. In this case report, we present the clinical features, diagnostic evaluation, and management of a 46-year-old female with THS. The patient initially presented with right-sided peri-orbital pain, swelling, chemosis, and headache. Ocular examination revealed mild to moderate proptosis, complete ophthalmoplegia, and normal findings in the left eye. Imaging studies, including CT and contrast-enhanced MRI, confirmed the presence of non-specific inflammation in the cavernous sinus and associated structures. Immediate treatment with oral Prednisolone led to a significant reduction in symptoms within five days, with complete resolution of chemosis and pain. Ocular movements gradually improved over the following week. Long-term follow-up showed no recurrence of symptoms. Keywords: Chemosis; Ophthalmoplegia; Cavernous Sinus.